Development of the annelid axochord: insights into notochord evolution - Lauri, Antonella; Simakov, Oleg; Arendt, Detlev (Science, 2014)
Origin of the spine lies in a worm the notochord, the developmental backbone precursor, defines chordates—the group of animals to which humans belong. The origin of the notochord remains mysterious. Lauri et al. report the identification of a longitudinal muscle in an annelid worm that displays striking similarities to the notochord regarding position, developmental origin, and expression profile. Similar muscles, termed axochords, are found in various invertebrate phyla. These data suggest that the last common ancestor of bilaterians already possessed contractile midline tissue that, via stiffening, developed into a cartilaginous rod in the chordate line. Science, this issue p. 1365. The origin of chordates has been debated for more than a century, with one key issue being the emergence of the notochord. In vertebrates, the notochord develops by convergence and extension of the chordamesoderm, a population of midline cells of unique molecular identity. We identify a population of mesodermal cells in a developing invertebrate, the marine annelid Platynereis dumerilii, that converges and extends toward the midline and expresses a notochord-specific combination of genes. These cells differentiate into a longitudinal muscle, the axochord, that is positioned between central nervous system and axial blood vessel and secretes a strong collagenous extracellular matrix. Ancestral state reconstruction suggests that contractile mesodermal midline cells existed in bilaterian ancestors. We propose that these cells, via vacuolization and stiffening, gave rise to the chordate notochord. A comparative study suggests that the chordate notochord evolved from a ventral midline muscle in bilaterian ancestors. A comparative study suggests that the chordate notochord evolved from a ventral midline muscle in bilaterian ancestors.